MightyU – A portable sensor-based video game application for exercise training of children and adolescents with cerebral palsy - Lynn Eitner; Lennart Lücke; Elnaz Farshadfar; Christian Grüneberg; Christoph Maier; Almut Weitkämper; Bettina Menzen; Anja Burmann; Roman von Gehlen; Peter Konrad; Thomas Immich; Britta Karn; et al. (PLoS ONE, 2026)
Introduction To prevent therapy fatigue and maintain motivation for daily home muscle training is important for children with cerebral palsy (CP). Therefore, we developed the computer-based Motion-controlled training tool MightyU. Its feasibility, short-term effectiveness and acceptance of the game in daily muscle training at home was now tested in children with varying degrees of motor impairment. Methods A surface electromyography sensor detects muscle activation, which is translated into in-game actions. In this way, targeted muscle activity is used to collect coins during gameplay. 19 children with CP tested MightyU at home for a week on a predetermined muscle group of the upper or lower limbs. The feasibility analysis considered the number of refusals to participate in the study, voluntary use at home and feedback based on the Game Experience Questionnaire (GEQ). The evaluation of usability based on modified System Usability Scale (SUS). The training effect was assessed by analyzing the difference between collected coins before and after a one-week training. Results MightyU was refused by 2 of 21 children, 19 children (N = 9 female, 11.3 ± 2.9 years, gross motor function classification scale GMFCS I-IV) used it at home without adverse effects. All children and their families exhibited great interest in this game independent of age, intelligence quotient, severity of disability, targeted movement, and prior experience with computer games. Key results from the GEQ were positive, yet children evaluated the gaming experience more positively to their parents across all categories. Median SUS score was 83.3% (IQR: 75.0–91.7) for children and 79.2% (IQR: 66.7–91.7) for parents, indicating good perceived usability. Training led to improvement in collecting coins (41% increase). Conclusion There is a fundamental interest amongst children with CP and their families for the pioneering therapy option MightyU due to its user satisfaction and usability, thereby potentially augmenting patient autonomy and compliance.